Potensi financial distress perusahaan sektor hotel, restoran dan pariwisata syariah selama masa pandemi Covid-19 - Muhammad Taufiq Abadi (LPMP Imperium, 2022)
This study aims to determine and calculate the score of financial distress by using the financial ratios Altman Z-Score model. In addition, this research also aims to determine the liquidity ratio, profitability, leverage, market testing, and activity will significantly contribute to the discriminant equation. Data were collected from Shariah hotel, restaurant, and tourism sub-sector companies listed on the stock index Indonesian sharia before and during the covid-19 pandemic. Research result shows that using the Altman model, two companies in 2019 and 4 companies in 2020 have the potential to experience financial distress. Besides the results, research shows a significant influence between the liquidity ratio, profitability, and leverage on the Altman Z-Score discriminant equation. Then the results of subsequent research show a significant difference between the Altman Z-Score model in predicting financial distress in sub-company the hotel, restaurant, and sharia tourism sector listed on the Indonesian sharia stock index before the pandemic and during the covid-19 pandemic.